Pendampingan Hukum bagi Diaspora Indonesia di Korea Selatan - Herlindah Herlindah; Ranitya Ganindha; Syahrul Sajidin; Yasniar Rachmawati Madjid (Pustaka Peradaban, 2025)
The Faculty of Law, Universitas Brawijaya (FHUB) conducts a community service program as an implementation of the university's tridharma (three pillars of higher education), one of which is through collaboration with the international institution Korea Moslem Federation (KMF). This activity aims to provide legal understanding and assistance in addressing legal issues faced by the Muslim diaspora in South Korea, particularly in the areas of family law (marriage, divorce, child custody), inheritance law, and employment issues. The implementation scheme involves a non-university partner (scheme B), with two main forms of activities: legal counseling and technology-based consultation services. The FHUB-KMF cooperation is formalized in a Cooperation Agreement (PKS) and a Memorandum of Agreement (MoA), and is strengthened by previous experiences in joint research, public lectures, and community service. As an official institution in South Korea, KMF has the authority to resolve Islamic religious matters, so legal assistance from FHUB is expected to provide concrete solutions to the problems faced by the Muslim community there. Fakultas Hukum Universitas Brawijaya (FHUB) menjalankan program pengabdian masyarakat sebagai implementasi tridharma perguruan tinggi, salah satunya melalui kolaborasi dengan lembaga internasional Korea Moslem Federation (KMF). Kegiatan ini bertujuan untuk memberikan pemahaman hukum dan asistensi dalam menghadapi permasalahan hukum yang dialami diaspora Muslim di Korea Selatan, khususnya dalam bidang hukum keluarga (perkawinan, perceraian, waris) dan jaminan produk halal. Skema pelaksanaannya melibatkan mitra non-perguruan tinggi (skema B), dengan dua bentuk utama kegiatan, yaitu penyuluhan hukum dan layanan konsultasi berbasis teknologi. Kerja sama FHUB-KMF telah tertuang dalam Perjanjian Kerja Sama (PKS) dan Memorandum of Agreement (MoA), serta diperkuat oleh pengalaman sebelumnya dalam riset bersama, kuliah umum, dan pengabdian masyarakat. Sebagai lembaga resmi di Korea Selatan, KMF memiliki otoritas dalam menyelesaikan persoalan keagamaan Islam, sehingga pendampingan hukum dari FHUB diharapkan dapat memberikan solusi konkret bagi permasalahan yang dihadapi komunitas Muslim di sana.